2016
DOI: 10.1089/can.2015.0003
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Medical Cannabis Among Licensed Patients in Israel

Abstract: Objectives: To evaluate adherence among Israeli patients who are licensed to use medical cannabis and to identify factors associated with adherence to medical cannabis.Methods: Ninety-five novice licensed patients were interviewed for this cross-sectional study. The questionnaire measured demographics, the perceived patient–physician relationship, and the level of patients' active involvement in their healthcare. In addition, patients were queried about adverse effect(s) and about their overall satisfaction fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…In Israel, one cross-sectional study examined factors associated with the extent to which a patient takes MM as prescribed among those with a MM license (Zolotov et al, 2016). Patient’s level of participation in their healthcare (AOR=1.13, 95% CI: 1.03–1.24) and patients’ perceived relationship between them and their physician (AOR=1.40, 95% CI: 1.11–1.77) were positively associated with adherence to MMU.…”
Section: Resultsmentioning
confidence: 99%
“…In Israel, one cross-sectional study examined factors associated with the extent to which a patient takes MM as prescribed among those with a MM license (Zolotov et al, 2016). Patient’s level of participation in their healthcare (AOR=1.13, 95% CI: 1.03–1.24) and patients’ perceived relationship between them and their physician (AOR=1.40, 95% CI: 1.11–1.77) were positively associated with adherence to MMU.…”
Section: Resultsmentioning
confidence: 99%
“…The patient–physician relationship and patient activation were associated with medical cannabis adherence and predicted better health outcomes and health behaviors. 31 Data on adherence to medical cannabis treatment could inform treatment outcomes and effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect is also important because it has been found that experiencing a cannabis‐related AE (i.e. dizziness, fatigue, mild anxiety and feeling “weird”) is more common among nonadhering patients than among adhering ones . Thus, improving patients' education on cannabis treatments, could improve their therapy compliance, and reduce nonadherence affects, in particular psychiatric and nervous system AEs.…”
Section: Discussionmentioning
confidence: 99%